T. S. Eliot’s “Burnt Norton”: Past, Present, and Future - Hargrove, Nancy D. (Complutense Journal of English Studies, 2014)
Critical interpretations of “Burnt Norton” have varied widely over the nearly 80 years since its first publication. While many early scholars saw it as an abstract meditation on philosophy, the revelation in the 1970s, 1980s, and 1990s of the relationship of Eliot and Emily Hale changed to some extent the way in which it is read, with more of a personal view, at least in its inspiration. Indeed, I suggest that “Burnt Norton” and specifically the rose garden passage presents the two figures in the poem at a moment fraught with the possibility of rekindling their earlier romance. Our knowledge of the subsequent poems and of the failure of the further development of their relationship greatly colors our reading of the poem, preventing us from seeing the tension and suspense of this experience as it balances between the attraction of human love and that of a demanding spiritual commitment.